PENYEMAIAN DAN PENANAMAN RHIZOPHORA APICULATA DI DAERAH PASCA PENAMBANGAN TIMAH INKONVENSIONAL (TI) DI MUARA KUDAI KABUPATEN BANGKA - U Umroh (Jurnal Kelautan, 2015)
Mangrove forest at the Kudai Estuary, Bangka has destructed, caused by tin mining unconventional  activities (TI). Mangrove conversion to non-conventional mining affected directly or indirectly for mangrove (Rhizophora apiculata) ecosystem. Based on the condition, rehabilitation needed to do straightforward to sustainability and sustainable aspect. Aims of the study were cultivated planting analysis of mangrove at Kudai Bangka Regency and to observed the participation on mangroves planting. This research was conducted on April 2010 to August 2011. Planting has done on tin post-mining Kudai Estuary, Bangka. The results showed that the seeding accomplishment are 100% and planting 99,6%. Substrat composition on tin post-mining area at Kudai Estuary are 60% sand, 30% clay and suitable substrat for mangrove (Rhizophora apiculata) growth. The seedling accomplishment and planting were supported by environmental parameters, such as pH, salinity, substrate, and organic materials.Keywords: Devastation, Unconventional Tin Mining (TI), Planting, Rhizophora apiculata